DIGITAL TRANSFORMATION IN NOTARY PRACTICE: IMPLEMENTATION OF ELECTRONIC CERTIFICATES FOR AUTHENTIC DEEDS BASED ON THE NOTARY OFFICE LAW - Maulita Tri Rosida; Rusdianto Sesung (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Technological developments have brought a wave of digital transformation that has spread across various sectors of life, including the world of notarial practice in Indonesia. This research is designed to examine how notaries actually implement electronic certificates (SE) in the process of creating authentic deeds. This study specifically focuses on Law Number 2 of 2014 concerning the Office of Notaries (UUJN) and examines its relationship with the Electronic Information and Transactions Law (UU ITE). The use of electronic certificates and electronic signatures (TTE) essentially offers great promise: efficiency, speed, and increased security for legal documents, a step forward that aligns with the ideals of a "Cyber ​​Notary." However, our investigation revealed gaps or normative discrepancies. On the one hand, the UUJN still firmly requires the physical presence of the parties and the written form of the deed on paper. On the other hand, the ITE Law has been much more progressive in recognizing the validity of electronic documents. This regulatory gap is very pronounced. The absence of explicit regulations governing electronic authentic deeds created by notaries has created legal uncertainty surrounding their evidentiary validity. Therefore, this study emphasizes the crucial need for regulatory harmonization. Furthermore, the development of an integrated digital infrastructure is crucial to ensure complete legal certainty and protection for both the public and notaries in the digital era.